EFEKTIVITAS KONSELING BAGI ORANG TUA BEKERJA UNTUK MEMPERBAIKI KUALITAS PEMBIMBINGAN BELAJAR KEPADA ANAK - Putri Saraswati (Jurnal Psikologi Tabularasa, 2010)
Abstract The purpose of this research is to explain the effectiveness of counseling for working parent to improve the quality of child's learning guidance. The research is conducted for M by reason of her demanding working schedule. Moreover, M holds the responsibility for guiding her child in studying. M tends to show aggressive behavior (threaten, frighten, snarl) when guiding her childs studying. The intervention which is chosen is counseling aiming for giving insight to M in terms of her and her childs condition, as well as providing correction for her misbehavior, when conducting guidance in her childs studying. Thus it is expected to be able to change Ms attitude and behavior for the quality improvement of study guidance. The design of research is case study with single case. Based on the research, it is explained that the subject is aware of her and her childs condition when conducting the guidance and realizes that her attitude and behavior in conducting the guidance is not appropriate. However, the subject does not have a will to change her aggression properly. Keyword: Working Parent, Counseling, Guidance